An algorithm to configure a large-scale monitoring network for parameter estimation of distributed systems - Ucinski, Dariusz (ECC : 2007 European Control Conference : 2-5 July 2007, 2007)
A computational procedure is presented for the design of a network of observation locations in a spatial domain that are supposed to be used while estimatng unknown parameters of a distributed parameter system. The problem is formulated as the determination of the density of gaged sites so as to maximize the log-determinant of the Fisher information matrix associated with the estimated parameters, subject to inequality constraints incorporating a maximum allowable sensor density in a given spatial domain. The search for the optimal solution is performed using a simplicial decomposition algorithm in which the restricted master problem reduces to an uncomplicated multiplicative weight optimization algorithm. The use of the proposed approach is illustrated by a numerical example involving sensor selection for a two-dimensional diffusion process.